Relathionship Relationship Between Fulfillment Of Pre-Operative Fluid Needs And The Incidence Of Nausea And Vomiting In Patients Post General Anesthesia At Dr Saiful Anwar Hospital, East Java Province - Shaumi Miftahul Rasyida; Achmad Dafir Firdaus; Sismala Harningtyas (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
Introduction: Postoperative nausea and vomiting, known as Postoperative Nausea Vomiting (PONV), is one of the problems often experienced by post-operative patients. Most anesthetic drugs have a vasodilation effect which causes hypotension and hypoperfusion, thereby stimulating the CTZ to produce nausea and vomiting reactions. Hypotension will be more dangerous if the body's fluid needs are not met at the time of surgery. Hypotension is one of the triggers that can cause nausea and vomiting. Giving fluids to preoperative patients is generally done to prevent intraoperative hypotension. Methods: The design of this research is analytical observational with a cross sectional approach, using a proportional sampling technique with a sample of 80 respondents. This research instrument uses the RINVR observation sheet and fluid calculations based on the fresh holiday formula. Data analysis using the Fisher Test with SPSS IBM Version 23. Results: The results showed that the majority of respondents, namely 72 (90%) channeled preoperative fluid requirements less than required, 44 respondents (55%) experienced mild nausea and vomiting, 61.1% Respondents experienced mild nausea and vomiting while meeting inadequate preoperative fluid requirements. The results of the Fisher Test statistical test obtained a value of p = 0.001, which can be concluded that there is a significant relationship between preoperative fluid requirements and the incidence of nausea and vomiting in patients after general anesthesia at RSUD dr. Saiful Anwar, East Java Province. Conclusions: In preoperative patients, a lot of fluid is lost. Fluid lost during fasting is replaced by calculating fluid requirements per day (per hour), calculating the fasting deficit (length of fasting) or dehydration (degree of dehydration). Providing sufficient fluids can reduce the risk of postoperative nausea and vomiting under general anesthesia.